Pharmacogenetics in transplant patients: can it predict pharmacokinetics and pharmacodynamics? - Burckart, Gilbert J; Liu, Xiaomei I (Therapeutic drug monitoring, 2006)
Pharmacogenetics holds the potential to allow individualized dosing of immunosuppressive agents to optimize their therapeutic effect while minimizing adverse effects. As more pharmacogenetic information accumulates, the prospect of reducing or discontinuing the intensive therapeutic drug monitoring of immunosuppressants looks attractive. However, the long process of developing useful clinical information from basic information on the genes of interest is at a very early stage, and our present information does not supercede pharmacokinetic or blood concentration monitoring of immunosuppressants. The most extensive blood concentration/dose information available is on tacrolimus and its dosing related to CYP3A5 and ABCB1 gene polymorphisms. Although CYP3A5 genotype is definitely associated with tacrolimus dosing, the only recommendation presently published is for an arbitrary doubling of the starting tacrolimus dose in CYP3A5 expressors. For cyclosporine, sirolimus, and corticosteroids, the presently available pharmacogenetic information does not permit pharmacokinetic predictions. The pharmacodynamics of immunosuppressants, as evidenced by effects on acute rejection or adverse drug effects, have considerably more potential for prediction by pharmacogenetic models. Drug-resistant rejection, nephrotoxicity, steroid resistance and osteonecrosis, and even patient survival may ultimately be predicted by models incorporating multiple gene polymorphisms and other critical patient information. At this point, treatment algorithms can be developed that will allow us to individualize a transplant patient's immunosuppressive therapy.